Calibrating conservation: new tools for measuring success - and Kapos, Valerie; Balmford, Andrew; Aveling, Rosalind; Bubb, Philip; Carey, Peter; Entwistle, Abigail; Hopkins, John; Mulliken, Teresa; Safford, Roger; Stattersfield, Alison; Walpole, Matt; Manica, Andrea (Conservation Letters, 2008)
Conservation practitioners, policy makers, and donors agree that there is an urgent need to identify which conservation approaches are most likely to succeed in order to use more effectively the limited resources available for conservation. While recently developed standards of good practice in conservation are helpful, a framework for evaluation is needed that supports systematic analysis of conservation effectiveness. A conceptual framework and scorecard developed by the Cambridge Conservation Forum help to address common constraints to evaluating conservation success: unclear objectives, ineffective information management, the long time frames of conservation outcomes, scarcity of resources for evaluation, and lack of incentives for such evaluation. For seven major categories of conservation activity, the CCF tools help clarify conservation objectives and provide a standardized framework that is a useful basis for managing information about project outcomes and existing conservation experience. By identifying key outcomes that can predict conservation success and can be assessed in relatively short time frames, they help to make more efficient use of scarce monitoring and evaluation resources. With wide application, the CCF framework and evaluation tool can provide a powerful platform for drawing on the experience of past and ongoing conservation projects to identify quantitatively factors that contribute to conservation success.
Keywords: Conservation effect; Conservation outcomes; Evaluation; Evidence-based conservation; Monitoring; conservation impact; framework; indicators; scorecard